2021
DOI: 10.37119/ojs2021.v27i1.510
|View full text |Cite
|
Sign up to set email alerts
|

Pay Attention to This: A Knowledge Translation Study of ADHD and its Brain Basis to Preservice and In-Service Teachers

Abstract: The purpose of the present study was to develop a knowledge translation (KT) activity for educators about the brain in children and adolescents with attention deficit hyperactivity disorder (ADHD). The goal was to increase our participants’ knowledge about ADHD and its brain basis. In addition to neuroscience content, the KT activity included the personal story of the lead researcher’s lived experience with ADHD to provide context, and to inform the participants’ perceptions of ADHD. Framed in an action resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The aggregate qualitative results signaled that pre-service teachers have a great deal of personal experience with individuals with ADHD (through themselves, family members, colleagues, or students), but do not necessarily know or understand the underlying neuroscience or cause for behaviors associated with ADHD. As in the previous study (Isenor et al, 2021), pre-service teachers know a number of strategies available to them to support students with ADHD, but they do not appear to have a clear understanding as to how or why these strategies work or may be necessary. Neuroscience knowledge may help teachers implement these strategies effectively or more frequently.…”
Section: Summary Of Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The aggregate qualitative results signaled that pre-service teachers have a great deal of personal experience with individuals with ADHD (through themselves, family members, colleagues, or students), but do not necessarily know or understand the underlying neuroscience or cause for behaviors associated with ADHD. As in the previous study (Isenor et al, 2021), pre-service teachers know a number of strategies available to them to support students with ADHD, but they do not appear to have a clear understanding as to how or why these strategies work or may be necessary. Neuroscience knowledge may help teachers implement these strategies effectively or more frequently.…”
Section: Summary Of Resultsmentioning
confidence: 76%
“…In the previous study, qualitative results suggested that the personal story of the presenter with ADHD was very impactful in our neuroscience KT activity (Isenor et al, 2021). In the current study, we experimentally manipulated whether the content was presented in a personalized or depersonalized manner.…”
Section: Role Of Personal Storymentioning
confidence: 88%
See 1 more Smart Citation
“…The brain‐associated conditions included in the KT activity (SSDs, TBIs and ASD) were selected based on the extant literature, the outcomes from the interviews with front‐line housing support workers and the expertise of the research team. When creating a KT activity, it has been recommended to contextualize research through storytelling, thus appealing to both the logical and emotional sides of audiences (Bourbonnais & Michaud, 2018; Isenor et al, 2021). As such, before discussing the neurobiological underpinnings of each brain‐associated condition, a corresponding quote from the interviews was presented.…”
Section: Resultsmentioning
confidence: 99%
“…Our KT activity design was similar to previous neuroscience KT activities in that we combined neuroscience information with personal stories from individuals with lived experience (Isenor et al, 2021). Previous work used action research to integrate the neuroscience knowledge with the lived experiences of one of the academic researchers in order to develop an effective KT activity.…”
Section: Discussionmentioning
confidence: 99%